Tuning Isomerism Effect in Organic Bulk Additives Enables Efficient and Stable Perovskite Solar Cells - Zhang, Qi; Zhao, Qiangqiang; Wang, Han; Yao, Yiguo; Li, Lei; Wei, Yulin; Xu, Ruida; Zhang, Chenyang; Shalenov, Erik O.; Tu, Yongguang; Wang, Kai; Xiao, Mingjia (Nano-Micro Letters, 2025)
Organic additives with multiple functional groups have shown great promise in improving the performance and stability of perovskite solar cells. The functional groups can passivate undercoordinated ions to reduce nonradiative recombination losses. However, how these groups synergistically affect the enhancement beyond passivation is still unclear. Specifically, isomeric molecules with different substitution patterns or molecular shapes remain elusive in designing new organic additives. Here, we report two isomeric carbazolyl bisphosphonate additives, 2,7-CzBP and 3,6-CzBP. The isomerism effect on passivation and charge transport process was studied. The two molecules have similar passivation effects through multiple interactions, e.g., P = O···Pb, P = O···H–N and N–H···I. 2,7-CzBP can further bridge the perovskite crystallites to facilitates charge transport. Power conversion efficiencies (PCEs) of 25.88% and 21.04% were achieved for 0.09 cm2 devices and 14 cm2 modules after 2,7-CzBP treatment, respectively. The devices exhibited enhanced operational stability maintaining 95% of initial PCE after 1000 h of continuous maximum power point tracking. This study of isomerism effect hints at the importance of tuning substitution positions and molecular shapes for organic additives, which paves the way for innovation of next-generation multifunctional aromatic additives. Highlights: 1 By anchoring the perovskite sites with the functional groups of CzBP (P = O···Pb, N–H···I and P = O···N–H), the bulk nonradiative recombination is suppressed and ion migration is inhibited. Doping perovskite films with CzBP led to enhanced intercrystallite interactions in the bulk and improved photoluminescence quantum yield. 2 Using a typical electron-rich moiety as the π-linker to replace the classic alkyl spacer in CzBP facilitated the charge-carrier transport processes and the passivation effect of carbazole further contributed to high VOC. The optimized 2,7-CzBP-treated device achieves the highest power conversion efficiency (PCE) of 25.88%, with VOC of 1.189 V for 0.090 cm2 and the perovskite solar cell module with a PCE of 21.04% for 14 cm2. 3 For 2,7-CzBP, the more extended conjugation and the more linear molecular geometry result in a more effective improvement in the performance.